Effect of Mixing Ingredient on Compressive Strength of ISSA Concrete Containing Eggshell Powder - Tan, Yeong Yu; Doh, Shu Ing; Chin, Siew Choo (Universiti Malaysia Pahang, 2016)
Waste management is one of the alarming issues in developing country like Malaysia. It is reported that sewage sludge and eggshell waste are generated annually. The amount of waste is expected to increase from year to year. Thus it is viable to investigate the possibility to turn waste into suitable construction materials in concrete production. In this paper, sewage sludge and eggshell waste are treated and used as blended cement to reduce the use of cement consumption in concrete production. At early stage of research, mortar cubes of mm of cubes were cast to identify the optimum percentage of ISSA. At the second stage, only optimum percentage of ISSA concrete were added with difference percentages of eggshell powder and tested by slump test and compressive strength. All the specimens were subjected to water curing before undergo compressive strength test. The optimum of ISSA and eggshell powder were 10% and 15% which capable to use as partial cement replacement. The total cement replacement is 25%. The compressive strength result was 37% higher than normal plain concrete. On the right formulation, ISSA and eggshell can be used partial cement replacement that exhibit optimum strength.